Pemanfaatan E-Commerce Dalam Penjualan Produk Pertanian Untuk Menumbuh Jiwa Entrepreneur Pada Remaja Desa - Mesran, M.Kom, Mesran; Saputra, Imam; Suginam, Suginam (Journal of Social Responsibility Projects by Higher Education Forum, 2025)
The use of E-Commerce in selling agricultural products has become a breakthrough that can help develop economic potential in villages. This article aims to explore the potential of village teenagers in running agricultural businesses by utilizing e-commerce platforms as a medium for selling agricultural products. The community service method is carried out through training and guidance to village teenagers regarding online selling procedures, product management, marketing, and how to interact with consumers effectively. The results of this community service activity show an increase in teenagers' knowledge and skills in utilizing e-commerce as a marketing medium for agricultural products. Not only that, participation in this activity is also able to improve the entrepreneurial spirit of village youth and provide an understanding of the added value of agricultural products produced in their village. Apart from that, the formation of a collaborative network between village teenagers and business actors in the city is also one of the positive results of this activity. In the future, it is hoped that this community service activity can have a sustainable impact on improving the welfare of village communities, especially village teenagers who are involved in this activity. Thus, the use of e-commerce in selling agricultural products is not only a business opportunity, but also a way to form an independent and creative entrepreneurial spirit in the younger generation in the village